2014
DOI: 10.1093/intqhc/mzu071
|View full text |Cite
|
Sign up to set email alerts
|

Integrated care programmes for adults with chronic conditions: a meta-review

Abstract: ObjectiveTo review systematic reviews and meta-analyses of integrated care programmes in chronically ill patients, with a focus on methodological quality, elements of integration assessed and effects reported.DesignMeta-review of systematic reviews and meta-analyses identified in Medline (1946–March 2012), Embase (1980–March 2012), CINHAL (1981–March 2012) and the Cochrane Library of Systematic Reviews (issue 1, 2012).Main Outcome MeasuresMethodological quality assessed by the 11-item Assessment of Multiple Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
187
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(192 citation statements)
references
References 39 publications
4
187
0
1
Order By: Relevance
“…Ouwens et al (2005) conducted a metareview of 13 studies that focussed on identifying the characteristics of integrated care that were important in improving the care of chronically ill people, as well as their effectiveness. Martínez-González et al (2014), building on the work by Ouwens et al (2005), conducted a meta-review seeking to identify the principles that facilitate high-quality integrated care.…”
Section: Introductionmentioning
confidence: 99%
“…Ouwens et al (2005) conducted a metareview of 13 studies that focussed on identifying the characteristics of integrated care that were important in improving the care of chronically ill people, as well as their effectiveness. Martínez-González et al (2014), building on the work by Ouwens et al (2005), conducted a meta-review seeking to identify the principles that facilitate high-quality integrated care.…”
Section: Introductionmentioning
confidence: 99%
“…The median (interquartile range) duration of hospitalization for a COPD exacerbation was less for subjects in the intervention group (5 [3][4][5][6][7][8][9][10][11] d vs 8 [4 -18.5] d, P ϭ .045). Total in-patient hospital days and ICU days due to COPD exacerbations were significantly less for the intervention group (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Disease management can be broadly defined as a comprehensive strategy for improving overall health status and reducing healthcare costs in chronic conditions. 5 These programs are often conducted by physician extenders and may include education about the underlying disease, optimization of evidence-based medications, support from case managers, and institution of self-management principles. 6 …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Advances in telecommunication technologies have created new opportunities to provide telemedical care as complementary treatment to the medical management of HF patients. Meta-analyses have suggested that telemedicine can reduce morbidity and mortality in patients with these types of disorder.…”
Section: The Role Of Telemedicine In the Management Of Chronic Diseasmentioning
confidence: 99%
“…In reviews assessing these methods, telemedicine approaches range from computerbased support systems to ones founded on structured telephone support, or even to programs led by nurses and physicians. 2,6 It is thus difficult to have a definitive opinion based on what we know now on whether or not telemedicine has a significant role to play in HF management.…”
Section: The Role Of Telemedicine In the Management Of Chronic Diseasmentioning
confidence: 99%